Analisis Pembelajaran Pjok Pasca Pandemi Covid-19 di Tinjau dari Kurikulum Merdeka Belajar Kelas X di SMA Pangudiluhur Sedayu - Laurensius Wisnu Yulianto; Dody Tri Iwandana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The aim of the Freedom to Learn Curriculum policy is to encourage students to master various fields of knowledge with their areas of expertise, so that they are ready to compete in a global world. This policy provides an opportunity for students to choose the subjects they will take based on their own desires. The implementation of the Free Learning Curriculum policy encourages the learning process to become more autonomous and flexible. Education always seeks to create students who always update every time. Not only highly educated but able to become agents of change in small or large scope. The resulting changes and innovations are able to provide maximum contribution to the progress of a nation that has quality human resources. In writing this paper, the author uses qualitative research methods. Keyword : Curriculum, Free Learning, PJOK Learning.